Reproductive Health Access Among Deployed U.S. Servicewomen: A Qualitative Study. Issue 6 (1st June 2014) - Manski, Ruth; Grindlay, Kate; Burns, Bridgit; Holt, Kelsey; Grossman, Daniel
ABSTRACT: Servicewomen's reproductive health experiences during deployment are important given that the majority of women in the U.S. military are of reproductive age and that this population experiences a disproportionately high rate of unintended pregnancy. Few studies have explored women's reproductive health experiences and their perceived barriers and facilitators to health care access during deployment. From May 2011 to January 2012, we conducted 22 in-depth interviews with women in the U.S. military about their reproductive health experiences during deployment, including their access to health services. Participants identified a range of barriers to accessing medical care in deployment settings, including confidentiality concerns, lack of female providers, and health-seeking stigma, which were reported to disproportionately impact reproductive health access. Some participants experienced challenges obtaining contraceptive refills and specific contraceptive methods during deployment, and only a few participants received predeployment counseling on contraception, despite interest in both menstruation suppression and pregnancy prevention. These findings highlight several policy and practice changes that could be implemented to increase contraceptive access and reduce unintended pregnancy during deployment, including mandated screening for servicewomen's contraceptive needs before operational duty and at least annually, and increasing the number of female providers in deployed settings.